Price escalation of area surrounding properties along metro line using GIS, A comparative study of Mumbai metro and proposed Pune metro - Ushadevi Patil, Dr; U. Mithe, Omkar (International Journal of Engineering and Technology, 2018)
Introduction of a transit megaproject like Metro railway in any city is seen as the effective booster for real estate sector for that city. Many cities worldwide and in India also has witnessed a considerable increase in rates of properties located along metro lines, also the areas situated around metro stations within a 500 m buffer zone has both positive and negative impacts on their property values. It is not necessary that the properties will show only positive effect, sometimes it may happen that due to noise and increased presence of commuters caused by the metro railway the area in the immediate vicinity of metro railway may show negative impact i.e. rates may decrease in that area. Present project firstly focuses on finding out the effect of Mumbai metro line on surrounding area using GIS and then comparing those results for obtaining corresponding values for proposed Pune metro. Initially focus will be on Mumbai metro and outcome of the same will be evaluated for proposed Pune metro. The data required for project has been collected from various government agencies like MMRDA, PCNTDA and DRS. The paper concludes with the brief explanation of alternate method of carrying out the same study.
Keywords: Transit Oriented development (TOD); Impact of proximity; Geographical Information System(GIS); Metro Rail; DP’s